Vitamin C supplementation in pregnancy - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Vitamin C deficiency is a prevalent problem among pregnant women in developing countries. This review is undertaken to evaluate current literature on effect of vitamin C supplementation on the course and outcomes of pregnancy so as to recommend its supplementation or otherwise. Electronic search of Medline, PubMed, Health Internetwork access to Research Initiative (HINARI), and Google Scholar databases was conducted for articles from 1stJanuary, 1993 to 30thNovember, 2014 using keywords such as “micronutrients”, “vitamin C”, “ascorbic acid”, “vitamin supplementation”, and “nutrition in pregnancy”. Current evidence from developing countries where vitamin C is deficient among pregnant women has shown that vitamin C may reduce the incidence of some complications of pregnancy and therefore encourage their supplementation in pregnancy. Additional studies, however, are needed in different geographic regions to identify whether vitamin C supplementation in pregnancy results in functional and measurable outcomes for maternal and foetal health. These studies would enable the appropriate intervention strategies to be developed, implemented, and evaluated. Such efforts will require the collaboration and commitment of government agencies, health care providers, nutritionists, research institutions, and the community.